Effect of cold-water immersion duration on body temperature and muscle function - Peiffer, J. J.; Abbiss, C. R.; Watson, G.; Nosaka, K.; Laursen, P. B. (Journal of Sports Sciences, 2009)
This study compared the effect of 5, 10 and 20 min of cold-water (14°C) immersion on rectal and muscle temperature and neuromuscular function. Twelve cyclists performed four cycling time-to-exhaustion trials in hot conditions (40°C and 40%rh), followed 25 min later by cold-water immersion for 5, 10 or 20 min or 20 min in room temperature (24°C; control). Rectal temperature was measured continuously, and muscle temperature was measured before, immediately after and 45 min after the time-to-exhaustion-test, as well as before and after water immersion. Sixty-second maximal voluntary isometric torque and isokinetic torque of the knee extensors were measured before, immediately after and 55 min after time-to-exhaustion-test. A greater rate of decrease in rectal temperature was observed in all water immersion conditions 45-80 min after time-to-exhaustion-test compared with control. Compared with control, muscle temperature 45 min after time-to-exhaustion-test was lower for all water immersion conditions; however, muscle temperature was lower for the 10- and 20-min conditions compared with 5 min. Isometric torque measured 55 min after time-to-exhaustion-test was lower for all conditions. Isokinetic torque was lower for all conditions immediately and 55-min post-time-to-exhaustion-test. Of the durations measured, 5 min of cold-water immersion appeared as the most appropriate duration for reducing rectal temperature but limiting decreases in muscle temperature.